Shakespeare and the versification of English drama, 1561 - 1642 - Tarlinskaja, Marina Grigorʹevna (Ashgate, 2014)
Why study versification? versification analyses -- How it all began: from Surrey's Aeneid to Marlowe's Tamburlaine -- Early Elizabethan playwrights: Kyd, Marlowe, Greene, Peele, early Shakespeare, Henry VI and Arden of Faversham -- Shakespeare's versification: evolution. co-authored plays. A lover's complaint -- Jacobean and Caroline playwrights: from Shakespeare to Shirley -- Conclusions: versification 1540s-1640s